An Efficient and Recyclable Catalytic System: PdCl2-Dppc+ -PF6– -[bmim][PF6] for Heck Coupling Reaction - Liu, Liang; Ming Song, Xiao; Tao Guan, Jin; Yong Zhang, Zhi; Mei Wei, Ben (Asian Journal of Chemistry, 2015)
An efficient PdCl2-Dppc+-PF6–-[bmim][PF6] catalytic system has been developed for the Heck coupling reaction of various aryl iodides with olefins. The catalytic system allows the coupling reaction to proceed smoothly in excellent yields and can be recycled 5 times with minimal loss of activity.